All the light we cannot see [compact disc, unabridged] : a novel - Doerr, Anthony, 1973- (Simon & Schuster Audio, 2014)
Marie Laure lives with her father in Paris and is blind by age six. Her father builds her a model of their neighborhood, so she can memorize it and navigate the real streets. When the Germans occupy Paris, they flee to Saint-Malo on the coast. In Germany, Werner grows up enchanted by a crude radio he finds. He becomes a master at building and fixing radios, which wins him a place with the Hitler Youth. Werner travels throughout Europe, and finally to Saint-Malo, where his meets Marie Laure.